Diabetes self-management in socioeconomically vulnerable people: A feasibility study - Segura Cortes, José Camilo; Moreno Fergusson, María Elisa (Revista Cuidarte, 2023)
Introduction: Type 2 diabetes mellitus is a leading cause of morbidity and mortality worldwide, and its prevalence is even higher in middle- and low-income countries. Self-management is a strategy that has been shown to control chronic diseases. Objective: To determine the feasibility and preliminary efficacy of the AMAS + Vida educational intervention focused on health self-management in adults with type 2 diabetes in a primary health care facility in Neiva, Colombia. Materials and Methods: Feasibility study using a one-group pretest-posttest design to determine the preliminary efficacy of the intervention. Purposive sample of 36 adults with type 2 diabetes. The instruments used were a characterization form and the Partners in Health scale to measure self-management. Results: Thirty-one adults with diabetes completed the 3-month follow-up, most of whom were women with low socioeconomic and educational levels. The feasibility of the intervention was good. Participants significantly improved disease knowledge (p < 0.001), eating habits (p = 0.001), health self-management behaviors (p < 0.001), and decreased body mass index (p = 0.01). There were no significant changes in physical activity (p = 0.125). Discussion: Self-management-based interventions, structured according to the theory of adaptation to chronic illness, achieve health-promoting changes in people with diabetes. Conclusions: The intervention showed preliminary efficacy in the study group with good feasibility. Further experimental studies are recommended.How to cite this article: Segura Cortes José Camilo, Moreno-Fergusson María Elisa. Automanejo de la diabetes en personas socioeconómicamente vulnerables: estudio de factibilidad. Revista Cuidarte. 2023;14(3):e3102.  http://dx.doi.org/10.15649/cuidarte.3102
Keywords: Diabetes Mellitus, Type 2; Nursing; Self-Management; Health Education; Feasibility Studies